Lower Member Amputation in Patient with Total Hip or Knee Arthroplasty - Sánchez, J Passini; Lara, FJ Pérez; Moya, R Marín; Muñoz, H Oliva (Global Journal of Medical and Clinical Case Reports, 2017)
In recent years the incidence of both amputations as total joint replacement surgery of lower limbs has been increased. So it is not rare to find both circumstances in the same patient. We discuss about the technical problem of this eventuality.